Customer Satisfaction Mediates the Effect of Marketing Mix and Self Service Technology on Customer Loyalty - Musfiroh, Mila Fursiana Salma; Wal Faizah; Titik Hinawati; Laila Sabrina (Mutanaqishah: Journal of Islamic Banking, 2024)
This research aims to examine the influence of marketing mix and self service technology variables on customer loyalty for rahn products with customer satisfaction as a mediating variable. Marketing mix is a marketing strategy that involves four main elements, namely product, price, place and promotion. Meanwhile, self-service technology is business development carried out by a company by providing self-service innovation. This research uses quantitative research methods. The population in this study were customers of Rahn products at PT. Sharia Pawnshop, Pasar Wage Purwokerto Branch with a sample size of 95 respondents. The data obtained was analyzed using the Structural Equation Modeling (SEM) analysis technique with the alternative Partial Least Square (PLS) approach via SmartPLS 4.0 software. The research results show that only the product and promotion variables have an influence on customer satisfaction and the place variable has an influence on customer loyalty. Implications this research uses customer data on rahn products at the Sharia Pegadaian Pasar Wage Purwokerto in 2020-2022.